IMPACT OF THE ECONOMIC DOWNTURN ON HATE CRIME TENDENCIES - Isokaitė, Indrė (Teisė, 2015)
The article aims at identifying the tendencies of hate crime during the period of economic crisis. This is being achieved through the following tasks: defining the concept of hate crime for this research (chapter XXV of Lithuanian Criminal Code: crimes and misdemeanours against person’s equal rights and freedom of conscience) and explaining circumstances that encumber the establishment of the impact of economic factors on hate crime; analysing legal theories that list economic factors among the reasons of hate crime; identifying the dynamics of hate crime during the period of economic downturn in Lithuania and verifying whether the tendencies might have been influenced by other factors (amendments of regulation and structural reform). The analysis reveals that most legal theories (strain theory, theories of social disorganisation, resource competition) confirm the growth of hate crime during the period of economic recession: members of society usually have a negative attitude towards immigrants or other minorities as posing risk on social-economic stability and increasing competition in distribution of resources. Nevertheless, it is emphasized that the influence of economic crisis on the tendencies of hate crime is much more complex, existing on macro-level and on micro-level, where the manifestation of hate motivation in a particular person’s behaviour depends on many factors, including the formation of prejudice, level of self-control, being unemployed and uneducated that are often related with poverty. Therefore one may come across a position that hate crime is not related with economic factors. Legal analysis finds that during the economic crisis the number of registered hate crime in Lithuania (mostly comprised of incitement to hatred) has grown from some tenths to hundreds of such criminal offences per year. The author notices that the Criminal Code has been supplemented with several new criminal offences (public incitement to violence by publishing, distributing hate production, organising groups, also denial, trivialisation of international crimes, crimes of Soviet or Nazi regime), however, there are usually only few if any such criminal offences per year in practice. Thus neither the changes in regulation nor the reorganisation of a special unit in the General Prosecutor‘s Office had any significant impact on the established growth of hate crime. Case law of Lithuanian courts, where statements inciting to violence are used in the context of economic crisis in Lithuania and negative attitude is expressed towards immigrants, national, sexual or other minorities, confirm that economic downturn intensifies hate prejudice. Finally, it is concluded that despite the identified growth of hate crime economic crisis is not the only or a direct cause of hate crime, still, undoubtedly it stands among the factors intensifying such type of crime (especially incitement to hatred). Attention is also paid to the fact that a ‘hate culture’ or a ‘hate phenomenon’ remains among the most complex challenges for states.